2022
DOI: 10.1186/s12968-022-00858-0
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution non-contrast free-breathing coronary cardiovascular magnetic resonance angiography for detection of coronary artery disease: validation against invasive coronary angiography

Abstract: Background Coronary artery disease (CAD) is the single most common cause of death worldwide. Recent technological developments with coronary cardiovascular magnetic resonance angiography (CCMRA) allow high-resolution free-breathing imaging of the coronary arteries at submillimeter resolution without contrast in a predictable scan time of ~ 10 min. The objective of this study was to determine the diagnostic accuracy of high-resolution CCMRA for CAD detection against the gold standard of invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…Among all coronary segments with a luminal diameter ≥1.5 mm on the CTA images, a majority of the coronary segments on MRA were diagnostic. Furthermore, coronary MRA with CSAI in our study achieved satisfactory diagnostic accuracy within a shorter scan time comparable to previous noncontrast‐enhanced coronary MRA studies with 3D patch‐based low‐rank reconstruction 5,37 . The high specificity and NPV suggested that CSAI‐based coronary MRA might have a potential role as a rule‐out test for CAD.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Among all coronary segments with a luminal diameter ≥1.5 mm on the CTA images, a majority of the coronary segments on MRA were diagnostic. Furthermore, coronary MRA with CSAI in our study achieved satisfactory diagnostic accuracy within a shorter scan time comparable to previous noncontrast‐enhanced coronary MRA studies with 3D patch‐based low‐rank reconstruction 5,37 . The high specificity and NPV suggested that CSAI‐based coronary MRA might have a potential role as a rule‐out test for CAD.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, coronary MRA with CSAI in our study achieved satisfactory diagnostic accuracy within a shorter scan time comparable to previous noncontrast-enhanced coronary MRA studies with 3D patchbased low-rank reconstruction. 5,37 The high specificity and NPV suggested that CSAI-based coronary MRA might have a potential role as a rule-out test for CAD. The moderate PPV might primarily be due to the presence of many moderate (25%-49%) stenotic segments, overestimated by observers as ≥50% lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Only segments with the score of 3 or 4 assessed by two radiologists consistently were included in the final stenosis assessment compared with CCTA. We incorporated 8 coronary segments into the analysis refer to the classification of the American Heart Association ( 14 ), as follows: (segment 1) RCA proximal, (segment 2) RCA middle, (segment 3) RCA distal, (segment 6) LAD proximal, (segment 7) LAD middle, (segment 8) LAD distal, (segment 11) LCX proximal, and (segment 13) LCX distal. The third radiologist evaluated the image quality when two observers assessed differently in the axial orientation.…”
Section: Methodsmentioning
confidence: 99%
“…The publication years of these studies ranged from 2005 to 2022; 23 of these studies utilized 1.5 T MRI technology [ 13 25 , 28 , 30 , 31 , 33 37 , 44 46 ], while 11 utilized 3.0 T technology [ 26 , 27 , 29 , 32 , 38 43 , 45 ]. The countries of publication were diverse, with China having 11 reports [ 18 , 26 , 32 , 34 , 38 , 39 , 41 45 ], Germany having 8 reports [ 13 , 15 , 19 , 25 , 27 , 29 , 31 , 35 ], Japan having 7 reports [ 14 , 17 , 24 , 28 , 30 , 37 , 40 ], United Kingdom [ 21 , 46 ] having two reports and various other countries such as the United States [ 20 ], Korea [ 16 ], Switzerland [ 36 ], Portugal [ 33 ], Belgium [ 23 ], and Turkey [ 22 ] having one report each. In terms of study design, one study employed a prospective multicenter design [ 28 ], while 19 employed prospective single-center designs [ 13 15 , 17 , 21 , 23 , 25 27 , 29 32 , 37 39 , 43 46 ].…”
Section: Resultsmentioning
confidence: 99%